Reinforcing urban resilience through sound landfill management: Addressing global climatic challenges with novel solutions - Goh, Kai Chen; Kurniawan, Tonni Agustiono; Othman, Mohd Hafiz Dzarfan; Anouzla, Abdelkader; Aziz, Faissal; Ali, Imran; C. Casila, Joan Cecilia; Khan, Muhammad Imran; Zhang, Dongdong; Dai, Wei; Onn, Choo Wou; Seow, Ta Wee (elsevier, 2025)
This study explores the critical role of effective landfill management in enhancing urban resilience amidst the growing challenges of climate change. With global municipal solid waste projected to rise 69 % from 2016 levels to 3.4 billion tons by 2050, addressing improper waste disposal—currently affecting 67 % of waste—has become imperative. This mismanagement contributes significantly to environmental degradation, public health risks, and soaring economic costs, projected to increase by 154 % from 2020 to USD 640.3 billion by 2050 without intervention. The study emphasizes the necessity for advanced landfill technologies, such as bioreactor landfills, smart waste management systems, and the integration of digital twins and IoT. These innovations can enhance waste processing efficiency, cut greenhouse gas emissions, and yield economic benefits. For instance, bioreactor landfills can boost methane (CH₄) production by up to 49 %, facilitating renewable energy generation. Additionally, green infrastructure, waste-to-energy technologies, and improved landfill designs are proposed to mitigate the effects of climate change, including extreme weather events that threaten landfill integrity and emissions stability. Key findings highlight the importance of integrating landfill resilience into urban planning and sustainable waste management strategies. A holistic approach combining technology, policy reforms, and community participation is recommended to build robust urban waste management systems capable of withstanding climate-related challenges. This work underscores the transformative potential of advanced waste management technologies in achieving resilient and sustainable urban systems, contributing significantly to global efforts in combating climate change.